South Africa's anti-apartheid movement. (World Book's documenting history, 2011)
"A history of the anti-apartheid movement in South Africa, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.